(untitled) (Research, Society and Development, 2023)
In view of the growing concern about the environmental impacts related to the use of synthetic polymers, studies aimed at obtaining and applying polymeric materials from renewable sources have been increasing, such as the development of edible films based on natural polymers. Therefore, this work aimed to produce edible and biodegradable films using a matrix of polysaccharides (gum arabic, carboxymethylcellulose and sodium alginate) with the addition of anise essential oil (EO) for possible use in primary packaging for mixtures of box cake. The films obtained were evaluated for thickness analysis, water vapor permeability (WVP), solubility and mechanical properties. The film thicknesses were different, as the preparation conditions are not always the same. The WVP values increased significantly, on average 150%, in relation to the control films with the incorporation of EO emulsion and mainly gum arabic (GA). With the addition of GA in the AS and CMC films, the maximum tension and elongation decreased, since a smaller amount of energy was required for the rupture of the film when it suffered a mechanical stress. The solubilization of the films, in conditions close to the preparation of a cake in the mixer, proved to be efficient. With the development of this research, it was possible to achieve the initial objective of obtaining a satisfactory filmogenic solution and the formation of an edible package containing polysaccharides and fennel essential oil emulsion.